Maqasid al Shariah from The Perspective of Muhammad Said Ramadhan al Buti (D.2013): An analytical study / Methaq Sadeq Mahmood Hazaea Almaliki - Methaq Sadeq Mahmood, Hazaea Almaliki (2018)
This research is applied, analytical study of "the Purposes of Sharia at Mohammed Saeed Ramadhan Al-Bouti (d. 2013)" who is one of the scholars of Islamic thoughts. Al-Bouti delivered fatawa (rulings) of controversial nature before his departure of this life. The study aims at disclosing his personality, scholarly status, and those scholars he was influenced by their thoughts. It also focuses on the definition and explanation of purposes, their types and ranks, and the illustration of methods to reveal them. The study also attempts to identify the characteristics and bases whereby the purposes of Sharia are realized and differentiated. The last part is concerned with the application of these purposes in necessities, fatawa, and legal situations. The current study depends on the diachronic analysis: collecting data from Al-Bouti's books, biographies of Al-Bouti, and articles and books on Al-Bouti. Then the researcher is to attempt to identify the date of purposes in the fundamental books from the time of recording and writing the purposes, i.e., from the time of Imam AL-Shatibi until the era of Sheikh Al-Bouti. The researcher also uses the inductive approach in the quest of examining the purposes of Sharia at Al-Bouti in all of his oral and written productions, be hardcopies or electronic ones.The study arrives at some results, of which the most prominent ones are: The purposes at Al-Bouti can be classified into two types: general and private. The general purposes are common and basic, represented in the five universals and complementary purposes like easiness, lifting discomfort, mercy and justice. The private purposes are related to the ideology, rituals, and punishments. Al-Bouti had purposes revealed by methods like the inductive method, rationalization, close examination of the Companions and Arabic. He benefited from purity of his intent, open-mindedness, wide insights of other cultures. He recognized some traits which helped to identify controls of interest such as the only ranked five universals, his association of individual's purposes with the purposes of Sharia, control of the link between necessities and improvements and needs, and control of the relationship between public interest and the purposes. His fatawa were distinguished owing to his scholarly honesty, and his intermediate position along the continuum of scholars. He also showed a remarkable insight regarding fiqh and rulings, considering Sharia rulings. His vision of the Arab Spring was an independent, legal one related to the purposes and rules of Sharia, characterized with fiqh of consequences and impact. His position from Islamic movements was according to the dictates of Islamic Sharia. The final outcome of the current research is that Al-Bouti, whose fatawa and positions are in parallel with the rulings, purposes, and objectives of Islamic Sharia, is a unique scholar in his age.